External Confirmations: Study of the Circularization of Third Party - Kátia Lemos; Sara Serra; Sandra Rodrigues; Emília Gomes (Communications of International Proceedings, 2021)
The audit process culminates in issuing an opinion on the reliability of the financial statements. For this, the auditor needs to perform audit procedures that allow him to obtain sufficient and appropriate evidence, with external confirmation being one of the most relevant audit procedures in the audit process. In view of the above, this work aims to analyze the importance of external confirmations, specifically the circularization of third-party balances, as well as the methods for preparing them. After reviewing the literature, it is concluded that the external confirmation procedure is the most appropriate in the audit process when the risk of misstatement of an assertion is materially relevant and it is not possible to carry out alternative audit procedures. Therefore, this procedure is frequently used to validate bank balances, accounts receivable and payable, bad debts, provisions, loans obtained, contracts and transactions with third parties. However, in order to ensure the reliability of the responses obtained, it is necessary to observe some procedures in carrying out this process, which consist of selecting the accounts to be validated and the third parties to circulate, choosing the method to be used, preparing the confirmation request and choosing the form of sending the confirmation request. Given the scarcity of literature on the subject, we consider this study relevant for academics and professionals, as it portrays in detail the external confirmation procedure and its importance for the quality of the audit process.
Keywords: Auditing; Audit evidence; Circularization of third-party balances; External confirmations.